Metal-free, visible-light-enabled direct C3-H arylation of anthranils - Adak, Tapas; Hu, Chao; Rudolph, Matthias; Li, Jun; Hashmi, A. Stephen K. (Organic letters, 2020)
An eosin Y disodium salt-catalyzed photoredox C-H arylation of anthranils is reported. A variety of aryl diazonium tetrafluoroborates were used as aryl sources, providing the C3 cross-coupled products. The in situ generated reactive radicals were trapped by anthranils, providing an alternative method to transition-metal-catalyzed C-H arylations of anthranils. Gold-catalyzed downstream transformations demonstrate the synthetic potential of these valuable building blocks.
Gesehen am 25.08.2020